CHARACTERIZATION OF ACOUSTIC EMISSION PROPERTY RELATED TO PIPE LEAKAGE (CASE STUDY : WATER LEAKAGE IN A GALVANIZED STEEL PIPE ) - FIKRI YUDHI (13309045); Pembimbing: Dr.Ir. Ida Bagus Ardhana Putra; Dr. Iwan Prasetiyo, S.T., , AZWAR
Pipelines is a system for delivering fluids from one place to another. In order to maintain all pipes in good performance, a monitoring system on the pipe's condition is required. A problem occurs when a complex pipeline system that consists of pipes with kilometers in length and many branches, has to be monitored. To get appropriate monitoring results of such complex pipelines system, an acoustic emission method can be applied. In leak monitoring of a water pipeline system, the source of acoustic emission is stimulated by turbulences of water flowing through the leak hole. The turbulence will excite energy that create deformation phenomenon in the pipe material. An experimental rig using galvalnized steel is developed to analyze correlations between properties of the pipe leakages, acoustic emission signals and properties of the pipe material. The experiment results show that galvanized steel has a β (wave attenuation constant) value of 0,015/cm with dominant frequency lies between 300 Ã‚Â– 500 kHz. It is also indicated that the β value does not change when the fluid pressure is altered. The results also indicate that for leak diameter of ÃƒÂ˜=5mm with the fluid pressures under 5 bar and for leak diameter of ÃƒÂ˜=7mm with all liquid pressures, the measurement results cannot be concluded due to inconsistent phenomenon between measured parameters of the acoustic emission and physical phenomena of the β value.